2016
DOI: 10.1007/s10620-016-4246-7
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Endoscopically Visible Polypoid Adenomatous Lesions Within the Extent of Ulcerative Colitis Have an Increased Risk of Colorectal Cancer Despite Endoscopic Resection

Abstract: Objectives: Ulcerative colitis (UC) is associated with an increased risk of colorectal cancer (CRC). Few studies have looked at long term outcomes of endoscopically visible adenomatous lesions removed by endoscopic resection in these patients. We aimed to assess the risk of developing CRC in UC patients with adenomatous lesions that develop within the segment of colitis compared to the remainder of an ulcerative colitis cohort. Conclusions: The risk of developing CRC is significantly higher in UC patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Kisiel et al's study using high‐definition chromoendoscopy also showed no progression to cancer over an average follow‐up of a median of 4.5 years 34 . In two studies where chromoendoscopy was not used, there was progression to cancer at a rate of 25.0% (n = 3/12) over a median of 1.7 years 37 and 40.0% (n = 2/5) over a median of 4 years 36 . In the former study high‐definition white light colonoscopy and polypectomy were performed by accredited endoscopists 37 …”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Kisiel et al's study using high‐definition chromoendoscopy also showed no progression to cancer over an average follow‐up of a median of 4.5 years 34 . In two studies where chromoendoscopy was not used, there was progression to cancer at a rate of 25.0% (n = 3/12) over a median of 1.7 years 37 and 40.0% (n = 2/5) over a median of 4 years 36 . In the former study high‐definition white light colonoscopy and polypectomy were performed by accredited endoscopists 37 …”
Section: Resultsmentioning
confidence: 92%
“…Seven studies (five cohort studies and two case series) reported on cancer progression rates after endoscopic resection of polypoid HGD (Table 3). 33‐37,39,40 All of the studies reported on very small numbers of polypoid HGD, and based completeness of resection on endoscopist judgement rather than histological assessment. This was due to difficulty in histological assessment of resection margins as a result of diathermy artefact or piecemeal resection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Colon cancer is the third most commonly diagnosed cancer worldwide [1][2][3]; furthermore, its incidence has signi cantly increased recently [4] and is expected to further rise by 50% in the next ve years [5]. Epidemiological studies show that the causes of colon cancer are related to environmental, lifestyle, and genetic factors, and that age, intestinal polyps, and ulcerative colitis also represent high-risk factors [6,7]; however, the speci c pathogenesis of colon cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%